Epidemiology of Maxillofacial Fracture – A Hospital Based Study - Mahat, Arun Kumar; Gurung, Gopal; Shrestha, Merina; Chaudhary, Bishwanath (Journal of Nepalgunj Medical College, 2020)
Introduction: Maxillofacial trauma is the most common problem seen by maxillofacial surgeons in Nepal. The causes of facial fractures are road traffic accidents (RTA), assaults, falls, gunshot wounds, domestic violence, sports and work injuries. Maxillofacial injury varies from soft tissue injury to facial bone fractures. This study was conducted to assess the burden of maxillofacial trauma in mid-western and far-western regions of Nepal. Material and Method: Patients with maxillofacial fractures admitted in dental ward of NGMCTH, Kohalpur, from April 2017 to April 2019 were included in the study. Patients having soft tissue injury without facial bone fractures and OPD cases were excluded from the study. Patient demographics, mechanism of injury, associated soft tissue injury, accompanying injuries to other parts of body and facial bone fractures were recorded. Patient were treated by open reduction internal fixation or lateral compression splint with circum-mandibular wiring or managed conservatively as necessary. Result: A total of 87 patients were included in the study. The age of patient ranged from 2 years to 67 years with a mean of 26.87 years. Most of the injuries occurred between the age group of 20-29 years with male: female ratio 5.2:1. The most frequent cause of facial bone fracture was RTA (51.7%) and the most frequently fractured facial bone was mandible. Contusion 54(49.5%) was the most common associated soft tissue injury. Head injury 20(52.6%) was the most common accompanying injury to other parts of body. The mean duration of hospital stay was 6.29. Conclusion: Male patient in their third decade mostly had mandible fracture due to road traffic accident. Head injury was the most common accompanying injury. Contusion was the most common type of associated soft tissue injury.